Assessment of the influence of metal ions released from the fixed orthodontic appliances on the static friction and surface topography of stainless steel and I archwires: An in-vitro study - Hussein S Yakop; Sarmad S. Salih Al Qassar; Mahmood Ahmad Hamood Aljoubory (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Static friction force between the orthodontic brackets and wire impacts the sliding mechanics that affect teeth movements and treatment duration. This sliding media is jam-packed with released metal ions from the fixed appliances. This study aimed to assess the static frictional force and surface topography of stainless steel (SS) and I archwires in dry conditions and in media fully with metal ions that were released from fixed appliances. METHODS: In this research study, a set of 60 as-received straight archwires specimens (5 cm wire) were employed and categorized into two groups based on the material type [30 super elastics new I archwires gauge (0.018 × 0.014 inch) and 30 SS archwires 0.018 × 0.022" as a control]. The archwires' static friction force was measured while sliding a loaded Roth SS brackets (0.018") on the archwire using a universal tensile testing machine in dry and metal ions released media, while the surface topography was assessed using a noncontact AFM machine. RESULTS: The static friction of I archwire was significantly lower than the SS wire in dry condition. Metal ions media released from fixed appliances significantly reduced the Static friction compared to dry and wet conditions with deionized water for both wires. An Atomic Force Microscope machine surface roughness reports revealed that the highest mean of all three roughness parameters was found in the SS group, followed by I archwires in descending order. Additionally, metal ions media significantly reduce all roughness parameters.